A Longitudinal Study of Changes in the Shot Characteristics of Women Table Tennis Players: Analysis of the Olympic Semifinals and Finals of Women's Singles - Wang, Jie; Li, Mengqi; Xiong, Xi (Frontiers in Psychology, 2022)
This study aims to evaluate the changes of shot characteristics of elite women table tennis players through the longitudinal analysis of women’s singles finals and semi-finals from 2004 to 2021 Olympic Games. Thirteen games were selected, and the stroke position, stroke type, ball placement and stroke efficacy of 5877 shots were analysed using the notational analysis method. A chi-square test was used to test the whether the shot characteristics had changed between game years, and the adjusted residual was calculated to judge these changes. In the four dimensions, namely, stroke position, stroke type, ball placement and stroke efficacy, the shot characteristics of women table tennis players have changed with the year of the Olympic Games. The backhand stroke position has an upward trend from 55.0% to 58.1%, and the type of flip stroke has a downward trend from 7.6% to 2.1%. The ball placements of forehand and middle long have two fluctuations of first rising from 11.2% to 12.7% and 20.3% to 23.7% and then falling from 12.7% to 5.3% and 23.7% to 16.0%. Moreover, backhand long is being increasingly used. In the year of equipment change, the proportion of neutral stroke increases from 40.0% to 61.5%. Once the players have become adapted to the equipment, the proportion of neutral stroke decreases from 61.5% to 48.5%. The development trend of women table tennis players is that the extreme stroke will be further increasingly used. Results suggest that elite women table tennis coaches and players should focus on the technical training in the forehand and backhand positions, strengthen the practice of topspin and block and pay attention to the backhand long landing area. Women’s table tennis coaches and players also need to pay close attention to the possible impact of changes in rules and equipment and carry out targeted training in advance to minimise the impact on the stroke efficacy of players.